Diversity in Farm Production and Household Diets: Comparing Evidence From Smallholders in Kenya and Tanzania - Kissoly, Luitfred Donacian; Karki, Sabina Khatri; Grote, Ulrike (Frontiers in Sustainable Food Systems, 2020)
Farm production diversity is widely promoted as a strategy for enhancing smallholders’ food and nutrition security. Nonetheless, empirical evidence from the rural smallholder context is still mixed. This study compares the nature, determinants and influence of farm production diversity on household dietary diversity in rural and peri-urban settings in Kenya and Tanzania. Descriptive and econometric analyses are employed using household-level survey data from four counties in Kenya (n=1212) and two districts in Tanzania (n=899). Results show notable variations in farm production diversity in the two countries as well as varying levels of household dietary diversity. For both countries, results further show that, farm production diversity has a positive and significant influence on indicators of household dietary diversity. However, this influence is more pronounced to households in remote rural settings. In peri-urban and rural areas with better market access, production diversity is generally lower but dietary diversity higher. These findings imply that although production diversity remains an important factor in ensuring enhanced household dietary diversity, it is imperative for policies related to food and nutrition security to consider context specific production and market-related aspects of smallholder agriculture. That is, while interventions focusing on farm production diversity may be important in rural contexts with poor market access, addressing market related bottlenecks can be more beneficial in rural and urban areas with better market access.